Carborane-thiol protected copper nanoclusters: stimuli-responsive materials with tunable phosphorescence. Issue 6 (23rd January 2023) - Jana, Arijit; Jash, Madhuri; Dar, Wakeel Ahmed; Roy, Jayoti; Chakraborty, Papri; Paramasivam, Ganesan; Lebedkin, Sergei; Kirakci, Kaplan; Manna, Sujan; Antharjanam, Sudhadevi; Machacek, Jan; Kucerakova, Monika; et al.
Abstract : A new class of flexible tetranuclear copper nanoclusters protected by carborane-thiols having stimuli-responsive tunable solid state phosphorescence. Abstract : Atomically precise nanomaterials with tunable solid-state luminescence attract global interest. In this work, we present a new class of thermally stable isostructural tetranuclear copper nanoclusters (NCs), shortly Cu4 @oCBT, Cu4 @mCBT and Cu4 @ICBT, protected by nearly isomeric carborane thiols: ortho -carborane-9-thiol, meta -carborane-9-thiol and ortho -carborane 12-iodo 9-thiol, respectively. They have a square planar Cu4 core and a butterfly-shaped Cu4 S4 staple, which is appended with four respective carboranes. For Cu4 @ICBT, strain generated by the bulky iodine substituents on the carboranes makes the Cu4 S4 staple flatter in comparison to other clusters. High-resolution electrospray ionization mass spectrometry (HR ESI-MS) and collision energy-dependent fragmentation, along with other spectroscopic and microscopic studies, confirm their molecular structure. Although none of these clusters show any visible luminescence in solution, bright μs-long phosphorescence is observed in their crystalline forms. The Cu4 @oCBT and Cu4 @mCBT NCs are green emitting with quantum yields ( Φ ) of 81 and 59%, respectively, whereas Cu4 @ICBT is orange emitting with a Φ of 18%. Density functional theory (DFT) calculations reveal the nature of their respective electronic transitions. The green luminescence of Cu4 @oCBT and Cu4 @mCBT clusters gets shifted to yellow after mechanical grinding, but it is regenerated after exposure to solvent vapour, whereas the orange emission of Cu4 @ICBT is not affected by mechanical grinding. Structurally flattened Cu4 @ICBT didn't show mechanoresponsive luminescence in contrast to other clusters, having bent Cu4 S4 structures. Cu4 @oCBT and Cu4 @mCBT are thermally stable up to 400 °C. Cu4 @oCBT retained green emission even upon heating to 200 °C under ambient conditions, while Cu4 @mCBT changed from green to yellow in the same window. This is the first report on structurally flexible carborane thiol appended Cu4 NCs having stimuli-responsive tunable solid-state phosphorescence.